CNN with phonetic attention for text-independent speaker verification - Zhou, Tianyan; zhao, yong; Li, Jinyu; Gong, Yifan; Wu, Jian (Automatic Speech Recognition and Understanding Workshop, 2019)
Text-independent speaker verification imposes no constraints on the spoken content and usually needs long observations to make reliable prediction. In this paper, we propose two speaker embedding approaches by integrating the phonetic information into the attention-based residual convolutional neural network (CNN). Phonetic features are extracted from the bottleneck layer of a pretrained acoustic model. In implicit phonetic attention (IPA), the phonetic features are projected by a transformation network into multi-channel feature maps, and then concatenated with the raw acoustic features as the input of the CNN network. In explicit phonetic attention (EPA), the phonetic features are directly connected to the attentive pooling layer through a separate 1-dim CNN to generate the attention weights. With the incorporation of spoken content and attention mechanism, the system can not only distill the speaker-discriminant frames but also actively normalize the phonetic variations. Multi-head attention and discriminative objectives are further studied to improve the system. Experiments on the VoxCeleb corpus show our proposed system could outperform the state-of-the-art by around 43% relative.